Freedom of Expression in Universities and University Colleges - Mona Wille (Ed.) (Spartacus Forlag AS / Scandinavian Academic Press, 2020)
Liberal democracies are experiencing changes of policies in the name of security, populism, polarization and an increasingly hardened rhetoric in the exchange of opinions and beliefs. How does this environment affect the universities and university colleges that are expected, if not required, to constitute an arena for free and open debate, for curiosity-driven research, and democratic, open, and student-centred learning? When is interference with freedom of expression necessary in a democratic society? Is freedom of expression in universities under threat? And what can be done to safeguard academic freedom and freedom of expression on campus?
English